Optimization of Re-Fracturing Method and Fracture Parameters for Horizontal Well in Mahu Conglomerate Oil Reservoir - Yi, Yonggang; Wang, Lei; Li, Jie; Chen, Sen; Tian, Hui; Tian, Gang (Frontiers in Energy Research, 2022)
Mahu Oilfield, the largest conglomerate oilfield around the world, is facing the severe problems of rapid production decline and low recovery ratio. Re-fracturing of horizontal wells is an effective method to improve this situation. Study of horizontal well re-fracturing is increasing popularity recently, but the optimization of re-fracturing parameters has not been thoroughly investigated, especially for the conglomerate reservoir. The optimal selection of re-fracturing parameters such as length and conductivity are not clear, which has significant influence on re-fracturing treatment and economic cost. To fill this gap, a series of numerical models are established based on filed data to predict horizontal well production after re-fracturing. The parameters of primary hydraulic fractures are calculated by net pressure matching and are imported into the numerical models. A production matching is conducted to confirm the reliability of numerical models. The cumulative productions of different re-fracturing stimulation method including lengthening old fractures and perforating new fractures are simulated, and the corresponding re-fracturing parameters are optimized. The results have shown that the length of primary fractures is smaller than designed, which means lengthening old fractures is necessary. Lengthening old fractures and perforating new fractures between primary clusters can both increase the production. On the condition of same fracture length, the increasing ranges of production corresponding to perforating new fractures are larger than that of lengthening old fractures. Lengthening old fractures is particularly suitable to the situation that the length of primary fractures is smaller than designed, and the optimal value in lengthening half-length of old fractures is 160 m. By contrast, perforating new fractures between old clusters is applicable to the case that the cluster spacing of primary hydraulic fracturing is larger than 35 m, and the optimal fracture half-length is 140 m.